New tools for measuring global academic performance - Abubakar, Ahmed; Abdullah, Haim Hilman; Kaliappen, Narentheren (SAGE Publications, 2018)
The study is on performance measurement in academia. It aims at developing and validating the measurement scale for the performance of higher institutions. The items were developed based on the extant literature. Data were collected via an online survey in which a questionnaire link was sent to 269 vice chancellors/presidents of the sampled universities. A total of 133 responses were retrieved at the end of the data collection period. This study used proportionate random sampling for sample selection. The goodness of measures was checked via field experts, academicians, and data analysis with SPSS. Overall, the alpha coefficient was .974. The outcome of exploratory factor analysis (EFA) exposed all factors loaded more than 0.50. The results revealed that the instrument was reliable and valid. Hence, the instrument developed was suitable to be used in examining the performance of higher institutions.